2022
DOI: 10.1038/s41420-022-01193-0
|View full text |Cite
|
Sign up to set email alerts
|

The genesis and evolution of acute myeloid leukemia stem cells in the microenvironment: From biology to therapeutic targeting

Abstract: Acute myeloid leukemia (AML) is a hematological malignancy characterized by cytogenetic and genomic alterations. Up to now, combination chemotherapy remains the standard treatment for leukemia. However, many individuals diagnosed with AML develop chemotherapeutic resistance and relapse. Recently, it has been pointed out that leukemic stem cells (LSCs) are the fundamental cause of drug resistance and AML relapse. LSCs only account for a small subpopulation of all leukemic cells, but possess stem cell properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 115 publications
0
17
0
Order By: Relevance
“…The most characteristic transcriptomic signature of prMDS CD34+ cells distinguishing them from stMDS cells was the expression pattern of quiescent-like or slowly proliferating progenitors with LSC markers, and the signatures of processes that are associated with or regulate non-cycling malignant stem cells: that is, suppressed DDR and dysregulated adhesion pathways. 39 It is likely that the aforementioned changes in the cellular composition of CD34+ subpopulations between prMDS vs stMDS CD34+ cells (ie, their differentiation status) determine to some extent the differences in gene expression signatures. 38 We propose that prMDS CD34+ cells bear cell-autonomous and perhaps also noncellautonomous defects to establish a tumor-suppressing DDR barrier;…”
Section: Discussionmentioning
confidence: 99%
“…The most characteristic transcriptomic signature of prMDS CD34+ cells distinguishing them from stMDS cells was the expression pattern of quiescent-like or slowly proliferating progenitors with LSC markers, and the signatures of processes that are associated with or regulate non-cycling malignant stem cells: that is, suppressed DDR and dysregulated adhesion pathways. 39 It is likely that the aforementioned changes in the cellular composition of CD34+ subpopulations between prMDS vs stMDS CD34+ cells (ie, their differentiation status) determine to some extent the differences in gene expression signatures. 38 We propose that prMDS CD34+ cells bear cell-autonomous and perhaps also noncellautonomous defects to establish a tumor-suppressing DDR barrier;…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have recently revealed that AML patients have repeated mutations in several important epigenetic mediators [ 82 ]. Mutations in genes involved in DNA methylation, such as DNA methyltransferase 3A (DNMT3A) and isocitrate dehydrogenase 1 and 2 (IDH1/2), are the most common.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to their healthy counterparts, tumor cells not only consume glucose at an accelerated rate, but they also exhibit significantly increased demand for amino acids to support rapid growth and proliferation [ 64 , 65 ]. Recent studies have reported that Leukemic stem cells (LSCs), including those in AML, heavily rely on amino acid metabolism, crucial for maintaining their stemness.…”
Section: Interplay Between Autophagy and Amino Acids Metabolism In Am...mentioning
confidence: 99%